Moving forward a strategic plan for the packaging group of Lapanday Foods Corporation - Hernandez, Maria Corazon A. (School of Management, University of the Philippines Mindanao, 2007)
The demands of the business climate in the global economy require an enterprise to be agile and adaptable.